TRANSFORMASI PENDIDIKAN KARAKTER: PENGARUH KURIKULUM MERDEKA TERHADAP PESERTA DIDIK - Jihan Fauziah; Masnuripa Siregar, Nurul Syakirah Srg, Nurul Wardani Fadhila Lubis, Yunita Syahfitri (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Education plays a very vital role in human life. Through education, people can improve their quality of life and solve problems by thinking critically and practically. Education receives special attention as a forum for developing human resources. Every educational process in educational institutions requires a curriculum. When the curriculum undergoes change, a process is needed that involves all related parties, starting from the awareness that change is part of the life cycle of society. This research focuses on the influence of the Merdeka Curriculum on students. The transformation of character education and the impact of the Independent Curriculum on students requires case studies or concrete analysis regarding the implementation of this curriculum in the learning process to strengthen student character formation. The aim of this research is to understand the transformation of character education and the influence of the Independent Curriculum on students' character. This research uses a qualitative approach with interview methods and literature study methods by collecting relevant data and analyzing and studying it in detail and in depth, as well as holding discussions to discuss the context related to the material in the journal. From this research, 4 results were found, namely (1) Understanding of character education (2) The role of the curriculum in character formation, (3) Implementation of the independent curriculum in character education, (4) Challenges and opportunities in implementing the independent curriculum.